The Influence of Workload and Physical Work Environment on employee's work productivity with Employee Engagement as an Intervening Variable (Case Study at PT PLN (Persero) UPT Cirebon) - Nur Arifyanto, Aziz; Indiyati , Dian (International Journal of Science, Technology & Management, 2025)
PT PLN (Persero) Unit Pelaksana Transmisi Cirebon is a PLN Unit tasked with maintaining the operational reliability of High Voltage and Extra High Voltage electrical equipment in the West Java region. The company has an duty to transmit 100% of the power produced from power plants to customers. The situation observed over the last five assessment periods reveals that the number of the employee’s work productivity has been highly fluctuating. Employee’s work productivity is influenced by several factors, one of which is employee engagement. The 2023 Employee Engagement survey results indicate that Work Engagement has reached 88.93% of the 88% target. However, certain dimensions have not met the target, namely the Work Conditions dimension (85.84%), which includes two factors: workload and physical work environment. The workforce at PT PLN (Persero) UPT Cirebon is still understaffed (96.8%), leading to frequent and prolonged overtime work. The Physical Work Environment at PLN UPT Cirebon is also not entirely satisfactory due to malfunctioning work facilities and equipment. This research aims to determine the influence of Workload and Physical Work Environment on Employee Engagement and its implications for Employee’s Work Productivity at PT PLN (Persero) Unit Pelaksana Transmisi Cirebon. This study employs a quantitative method with a descriptive research type. The research respondents consist of 219 employees of PT PLN (Persero) UPT Cirebon, utilizing non-probability sampling with saturated sampling. The processed data will be analyzed using descriptive analysis techniques with SEM-PLS. This research hypothesizes that Workload and Physical Work Environment simultaneously have a significant influence on Employee Productivity through Employee Engagement as an intervening variable at PLN UPT Cirebon. The research results indicate that the Physical Work Environment has a positive and significant influence on both Employee Engagement and Employee’s Work Productivity. Similarly, Employee Engagement was found to have a positive and significant influence on Employee’s Work Productivity. However, Workload did not show a significant influence on either Employee Engagement or Employee’s Work Productivity, whether directly or through the intervening variable. A coefficient of determination value of 0.631 indicates that 63.1% of employee productivity is explained by these three variables, while the remainder is influenced by other factors. This research has limitations in its scope of the variables considered. Therefore, further research is recommended to explore other variables such as leadership style, work-life balance, organizational culture, or to conduct qualitative studies to gain a deeper understanding of the phenomena.